2022
DOI: 10.1002/jum.15951
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐Enhanced Ultrasound Features of Adult Xp11.2 Translocation Renal Cell Carcinoma

Abstract: Objectives To investigate the sonographic features in Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC) using both conventional ultrasound (US) and contrast‐enhanced US (CEUS) and evaluate the usefulness of sonographic imaging characteristics to differentiate between Xp11.2 tRCC and the three common RCC subtypes. Methods Thirty‐four adult Xp11.2 tRCC patients who preoperatively underwent both conventional US and CEUS and had solitary renal lesions and pathological confirmation after surgery were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…CEUS offers numerous advantages, including noninvasiveness, real-time imaging capabilities, and the accurate assessment of renal tumor characteristics and vascularity. In a study conducted by Ma et al ( 23 ), fast wash-out patterns were identified as the primary features of Xp11.2 RCC. Furthermore, Wei et al ( 24 ) investigated the differentiation between Xp11.2 RCC and clear cell type renal cell carcinoma (ccRCC) using CEUS and found that Xp11.2 RCC exhibited lower peak enhancement compared to ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS offers numerous advantages, including noninvasiveness, real-time imaging capabilities, and the accurate assessment of renal tumor characteristics and vascularity. In a study conducted by Ma et al ( 23 ), fast wash-out patterns were identified as the primary features of Xp11.2 RCC. Furthermore, Wei et al ( 24 ) investigated the differentiation between Xp11.2 RCC and clear cell type renal cell carcinoma (ccRCC) using CEUS and found that Xp11.2 RCC exhibited lower peak enhancement compared to ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to blood vessel abnormalities, including thickened vessel walls and variable amounts of slowly growing adipose tissue, with less frequent necrosis and ischemia in the adjacent renal parenchyma [ 24 ]. These characteristics explain a more frequent homogeneous pattern and the rare presence of the perilesional border, unlike RCCs [ 25 ]. Occasionally, AMLs, especially those larger than 4 cm, may display spontaneous hemorrhages with a heterogeneous pattern on CEUS [ 18 ].…”
Section: Qualitative Evaluation Of Rcc and Aml On Ceusmentioning
confidence: 99%